THE IMPACT OF PTSD TREATMENT ON THE CORTISOL AWAKENING RESPONSE. Issue 10 (October 2014) - Pacella, Maria L.; Feeny, Norah; Zoellner, Lori; Delahanty, Douglas L.
<x xml:space="preserve">Abstract</x> Background Posttraumatic stress disorder (PTSD) is associated with abnormal functioning of the hypothalamic–pituitary–adrenal (HPA) axis; however, limited research has examined whether cortisol levels change following successful PTSD treatment. The current study examined the impact of successful PTSD treatment on the cortisol awakening response (CAR). Method Twenty‐nine adults participating in a treatment trial for chronic PTSD provided saliva samples (upon waking, and 30‐, 45‐, and 60 min postwaking) before and after receiving either prolonged exposure therapy or sertraline. PTSD responder status (i.e., loss or retention of a PTSD diagnosis) served as the predictor variable. Outcome measures included area under the curve with respect to ground and increase, reflecting total cortisol output and HPA axis reactivity, respectively. Results A series of hierarchical regressions revealed no significant main effects of PTSD responder status for either CAR outcome. However, a significant gender by treatment response interaction for cortisol reactivity revealed that female treatment nonresponders displayed higher cortisol reactivity following treatment than female responders, whereas cortisol reactivity did not change pre‐ to posttreatment for male responders. Findings remained after controlling for age, trauma history, baseline medication status, baseline PTSD, and baseline depressive symptoms. Conclusion Loss of a PTSD diagnosis may contribute to decreased cortisol reactivity in females. Neuroendocrine changes following treatment may emerge only for specific subgroups, highlighting the importance of exploring treatment moderators.